Optimal cytoreduction followed by chemoradiation in stage IVB uterine serous carcinoma. (2022) - McEachron, Jennifer; Zhou, Nancy; Hastings, Victoria; Bennett, Michelle; Gorelick, Constantine; Kanis, Margaux J.; Lee, Yi-Chun
Highlights: Advanced uterine serous carcinoma (USC) carries a poor prognosis. Maximal cytoreduction is associated with improved survival in stage IVB USC. Chemoradiation may offer a survival benefit due to improved local control. Abstract: Objectives: The prognosis of patients presenting with stage IVB uterine serous carcinoma (USC) remains extremely poor, with a reported 5-year survival of <20%. Here were evaluate the survival impact of cytoreductive surgery and identify other prognostic factors in stage IVB USC. Methods: A multicenter retrospective analysis of patients with stage IVB USC was conducted from 2000 to 2018. Inclusion criteria were patients who had undergone comprehensive surgical staging/tumor debulking; followed by adjuvant chemotherapy+/-external beam radiation therapy (EBRT). Optimal cytoreduction (R1) was defined as residual disease ≤1 cm at completion of surgery, and suboptimal cytoreduction (R2) was defined as >1 cm. Progression free survival (PFS) and overall survival (OS) analysis was performed using Kaplan-Meier estimates. Multivariate analysis (MVA) was performed using Cox proportional hazards model. Results: Final analysis included 68 patients. There was no difference in the frequency of treatment delays between regimens ( p = 0.832). 96% of patients received platinum-based chemotherapy. There was no difference in the age ( p = 0.227), race ( p = 0.936), type of radiotherapy ( p = 0.852) or chemotherapy regimen received ( p = 0.996) between R1 and R2 cohorts. The median PFS for all patients was 8 months and the median OS was 13 months. Cytoreduction to R1 was associated with a median PFS of 9 months, compared to R2 with a median PFS of 4 months ( p < 0.001, HR 0.32, 95% CI 7.4–14.1). Median OS was also improved with R1 vs. R2 cytoreduction (17 months vs. 7 months, respectively) ( p < 0.001, HR 0.21, 95% CI 13.7–26.4). Compared to R1, cytoreduction to R0 was not associated with a survival benefit. The R0 median OS was 17 months versus 18 months in R1 ( p = 0.67). The combination of adjuvant chemoradiation was associated with improved PFS (11 months vs. 7 months) ( p = 0.024, HR 0.41, 95% CI 6.5–9.4) and OS (22 months vs 13 months) ( p = 0.65, HR 0.25, 95% CI 10.5–15.4) compared to chemotherapy-alone, respectively. On MVA, only the amount of residual disease ( p = 0.003, HR 0.39, 95% CI 0.2–0.7) and receipt of adjuvant chemoradiation ( p = 0.010, HR 0.09, 95% CI 0.01–0.58) were independent predictors of survival. Conclusions: In stage IVB USC, optimal cytoreduction should be the goal at the time of primary surgery. The combination of chemoradiation was associated with superior survival compared to chemotherapy alone and should be further investigated in this patient population.